Antioxidant and Anti-Inflammatory Activities of the Crude Extracts of Moringa oleifera from Kenya and Their Correlations with Flavonoids - Yong-Bing Xu; Gui-Lin Chen; Ming-Quan Guo (Antioxidants, 2019)
Moringa oleifera Lam. (M. oleifera) is commonly distributed and utilized in tropical and sub-tropical areas. There has been a large number of reports on the antioxidant and anti-inflammatory activity of its leaves, but only a few about its seeds and roots. Hence, in this work we aimed to systematically compare the antioxidant and anti-inflammatory activities of the ethanol crude extracts of leaves, seeds, and roots of M. oleifera from Kenya, and further correlate the differential activities with the chemical constituents from these three parts. The antioxidant activities were measured by using three different assays (DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS (2,2′-azinobis-(3-ethylbenzthiazoline-6-sulfonic acid) and FRAP (Ferric-Reducing Antioxidant Power), respectively). Results showed that the leaf extracts displayed the highest DPPH radical scavenging and FRAP total reducing power activities with IC50 values of 1.02 ± 0.13 mg/mL and 0.99 ± 0.06 mM Fe2+/g, respectively; the leaf and root extracts exhibited potential ABTS radical scavenging activities with the IC50 values of 1.36 ± 0.02 and 1.24 ± 0.03 mg/mL. Meanwhile, the leaf and seed extracts (11.1−100 µg/mL) also exerted obvious anti-inflammatory activities, as indicated by the inhibition of NO production. To further reveal correlations between these differential activities with the chemical constituents in the three organs, the total flavonoids content (TFC) of the three different extracts were evaluated, and the TFC of leaves, seeds and roots were found to be 192.36 ± 2.96, 5.89 ± 0.65 and 106.79 ± 2.12 mg rutin equivalent (RE)/g, respectively. These findings indicated the important impacts of the total flavonoid contents on antioxidant and anti-inflammatory activities. Additionally, we further determined the phytochemical profiles of M. oleifera by HPLC-UV/ESI-MS/MS, and identified most of the chemical constituents of leaves as flavonoids. In summary, the leaves of M. oleifera are a better potential natural source of antioxidants and anti-inflammatory agents, and very promising for development into the health promoting dietary supplements.